PROBLEMATIKA PELAKSANAAN ASESMEN NASIONAL BERBASIS KOMPUTER (ANBK) SEKOLAH DI KABUPATEN SERUYAN - Abdul Gofur (Adaara: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to explore the problems of the implementation of the Computer-Based National Assessment (ANBK) which was carried out at SMPN 1 and SMAN 1 Danau Seluluk, Seruyan Regency, which are schools that are geographically as well as located far from urban centers and the availability of internet networks is not optimal. The research method uses descriptive qualitative research. The research subjects in this study were school principals, vice principals and implementing proctors. The research results obtained in the field included, SMPN 1 and SMAN 1 Danau Seluluk implemented semi-online ANBK. This was done because the condition of the internet network was unstable, besides that the lack of complete ANBK facilities and infrastructure, this is evidenced by the limited number of laptops and computers available. Furthermore, students also experience difficulties in answering ANBK questions related to literacy and numeracy. This occurs because of the gap between the material provided by the teacher and the questions given at ANBK so that teachers need training and assistance in developing learning in accordance with the demands of ANBK.